Was The 2011 NATO-Led Intervention In Libya A Just War? - D’Alessio, Federico Alistair (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
This paper seeks to analyse the level of compliance of the 2011 NATO intervention in Libya with the principles of the just war doctrine: jus ad bellum, jus in bello, and jus post bellum. These principles indicate the right to go to war, right conduct in war, and justice after the war respectively. The first criterion appears to have been met, albeit showing some controversies around the hidden agenda of NATO. On the contrary, the right conduct in the war was nearly infringed in its entirety, apart from military necessity which showed a discreet level of conformity. Nevertheless, the principle of jus post bellum was completely disregarded, as the NATO powers did not collectively work to establish new political institutions able to build a democratic state: the country was left at its own destiny instead. This treatment of Libya led to serious consequences on social, political, and economical levels that affected both Africa and Europe.